Getting a grip on problem gambling: what can neuroscience tell us? - Goudriaan, Anna E.; Yücel, Murat; van Holst, Ruth J. (Frontiers in Behavioral Neuroscience, 2014)
In problem gamblers, diminished cognitive control and increased impulsivity is present compared to healthy controls. Moreover, impulsivity has been found to be a vulnerability marker for the development of pathological gambling (PG) and problem gambling (PrG) and to be a predictor of relapse. In this review, the most recent findings on functioning of the brain circuitry relating to impulsivity and cognitive control in PG and PrG are discussed. Diminished functioning of several prefrontal areas and of the anterior cingulate cortex indicate that cognitive-control related brain circuitry functions are diminished in PG and PrG compared to healthy controls. From the available cue reactivity studies on PG and PrG, increased responsiveness towards gambling stimuli in fronto-striatal reward circuitry and brain areas related to attentional processing is present compared to healthy controls. At this point it is unresolved whether PG is associated with hyper- or hypo-activity in the reward circuitry in response to monetary cues. More research is needed to elucidate the complex interactions for reward responsivity in different stages of gambling and across different types of reward. Conflicting findings from basic neuroscience studies are integrated in the context of recent neurobiological addiction models. Neuroscience studies on the interface between cognitive control and motivational processing are discussed in light of current addiction theories. Clinical implications: we suggest that innovation in PG therapy should focus on improvement of dysfunctional cognitive control and/or motivational functions. The implementation of novel treatment methods like neuromodulation, cognitive training and pharmacological interventions as add-on therapies to standard treatment in PG and PrG, in combination with the study of their effects on brain-behavior mechanisms could prove an important clinical step forward towards personalizing and improving treatment results in PG.